Development Strategy of Education Tourism in Cibodas Village In West Bandung Regency - SAEPUDIN, Encang; BUDIONO, Agung; HALIMAH, Mas (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018, 2019)
The desire of the community to obtain the entertainment and also getting new knowledge is a great opportunity for the development of educational tourism villages. This opportunity occurs because of the saturation in education development in the room. However, in the development of tourism villages we must give attention to the aspects of social life, culture, and livelihoods of rural communities. The purpose of the research is to find out the strategies for the development of educational villages based on the potential of tourism products. This study uses qualitative methods with a case study approach. The process of collecting data used is interviews, observation, F G D, and literature. Descriptive data analysis techniques with stages of data reduction, data presentation, and conclusion. Test Validity and reliability through the source triangulation process. Informants in this study were the government (3 people), community leaders and religion (5 people), and village tourism managers (5 people). The number of respondents is 13 people. The results of the study show that the development model of educational tourism villages in Cibodas Village has six strategies, namely (a) increasing active community participation in the development of tourism villages (b) the development of distinctive tourism villages based on the natural, social and cultural potential of the local community; (c) capacity building of community institutions as tourism village management institutions (d) development of tourism promotion media; (e) improvement of human resources through structured and organized education and training programs; (f) mentoring carried out in a structured manner from the relevant institution / agency.